Phenolic Hydroxyl Groups in the Lignin Polymer Affect the Formation of Lignin Nanoparticles - Jae Hoon Lee; Tae Min Kim; In-Gyu Choi; Joon Weon Choi (Nanomaterials, 2021)
Alkaline soda lignin (AL) was sequentially fractionated into six fractions of different molecular size by means of solvent extraction and their phenolic hydroxyl groups were chemoselectively methylated to determine their effect on nanoparticle formation of lignin polymers. The effect of the lignin structure on the physical properties of nanoparticles was also clarified in this study. Nanoparticles were obtained from neat alkaline soda lignin (ALNP), solvent-extracted fractions (FALNPs, i.d. 414–1214 nm), and methylated lignins (MALNPs, i.d. 516–721 nm) via the nanoprecipitation method. Specifically, the size properties of MALNPs showed a high negative correlation (R2 = 0.95) with the phenolic hydroxyl group amount. This indicates that the phenolic hydroxyl groups in lignin could be influenced on the nucleation or condensation during the nanoprecipitation process. Lignin nanoparticles exhibited high colloidal stability, and most of them also showed good in vitro cell viability. This study presents a possible way to control nanoparticle size by blocking specific functional groups and decreasing the interaction between hydroxyl groups of lignin.